Homology-based modeling of Universal Stress Protein from Listeria innocua up-regulated under acid stress conditions - Tremonte, Patrizio; Succi, Mariantonietta; COPPOLA, RAFFAELE; Sorrentino, Elena; Tipaldi, Luca; Picariello, Gianluca; Pannella, Gianfranco; Fraternali, Franca (Frontiers in Microbiology, 2016)
An Universal Stress Protein (USP) expressed under acid stress condition by Listeria innocua ATCC 33090 was investigated. The USP was up-regulated not only in the stationary phase but also during the exponential growth phase. The three dimensional (3D) structure of USP was predicted using a combined proteomic and bioinformatics approach. Phylogenetic analysis showed that the USP from Listeria detected in our study was distant from the USPs of other bacteria (such as Pseudomonas spp., Escherichia coli, Salmonella spp.) and clustered in a separate and heterogeneous class including several USPs from Listeria spp. and Lactobacillus spp. An important information on the studied USP was obtained from the 3D-structure established through the homology modelling procedure. In detail, the Model_USP-691 suggested that the investigated USP had a homo-tetrameric quaternary structure. Each monomer presented an architecture analogous to the Rossmann-like α/β fold with 5 parallel β-strands and 4 α-helices. The analysis of monomer-monomer interfaces and quality of the structure alignments confirmed the model reliability. In fact, the structurally and sequentially conserved hydrophobic residues of the β-strand 5 (in particular the residues V146 and V148) were involved in the inter-chains contact. Moreover, the highly conserved residues I139 and H141 in the region α 4 were involved in the dimer association and functioned as hot spots into monomer-monomer interface assembly. The hypothetical assembly of dimers was also supported by the large interface area and by the negative value of solvation free energy gain upon interface interaction. Finally, the structurally conserved ATP-binding motif G-2X-G-9X-G(S/T-N) suggested for a putative role of ATP in stabilizing the tetrameric assembly of the USP. Therefore, the results obtained from a multiple approach, consisting in the application of kinetic, proteomic, phylogenetic and modelling analyses, suggest that Listeria USP could be considered a new type of ATP-binding USP involved in the response to acid stress condition during the exponential growth phase.